ENGARUH PRESTASI BELAJAR FIKIH TERHADAP PENGAMALAN IBADAH MAHDHAH: DI MTS NEGERI BANJARANGSANA CIAMIS - latief, Wawan; Fitriyani, Fitriyani (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
This study aims to determine the influence of jurisprudenceachievement toward the practicing of mahdhah worship in MTs NegeriBanjarangsana students. This research uses a descriptive method with aquantitative approach. Data collection are taken from observation, interviewsand questionnaires. Quantitative data processing is completed throughdescriptive data processing with Rank Spearmans (Rs) correlation. Theinfluence of fiqh learning achievement toward the practice of mahdhahworship of MTs Negeri students is relatively high with a value of 0.63 with theresult of determination of 39.69% with a significant value of T count = 3627while ttable = 1.725.